The molecular genetics of colorectal neoplasia - Stanley R. Hamilton (1993)
The Commemorative Essays for the 50th year of GASTROENTEROLOGY provide a historical perspective on advances and accomplishments in understanding gastrointestinal diseases. The history of the molecular genetics of colorectal neoplasia undoubtedly occupies the smallest portion of the last half century that the Essays cover, because the entire body of knowledge has accumulated in less than a decade. Nonetheless, clinical application of this knowledge to impact on the incidence and mortality from colorectal cancer is now at hand.